(untitled) (مجلة إحالات, 2026)
This research aims atclarifying somefeatures of Pragmaticmeditation in proverbliterature in the book "JamharatAl’Amthal" composed by "AbuHilal Al-Askary" (310 H). This research focused on the most important concept and foundation developed in the western Pragmatic study such as: the concept of linguistic usage, speech act, context, principle of Speech cooperationand intention. This research also studied the clarification of proverb concept and its literarycategory and position, and its importance as it was clarified by Arabic culture and heritage. Thisresearch proved that Abu Hilal Al-Askary’sthought and studyof proverbs contain indicationsand featureswhich give a firm consolidation to numerous pragmatic concepts and rules in the Western study.